Diversity of Soil Insects in The Aiknyet Natural Tourism Area, West Lombok - Alhafizin, M.; Ilhamdi, Mohammad Liwa; Wirajagat, Gde Cahyadi (Jurnal Biologi Tropis, 2025)
Soil insects play a vital role in maintaining forest ecosystem functions, yet their diversity in Indonesian protected areas remains underexplored. This study aims to analyze the diversity, dominance, and evenness of soil insect communities in three habitat zones riparian, forest edge, and forest interior within Aiknyet Natural Tourism Forest, Lombok Barat. A descriptive quantitative approach was used, with data collected via pitfall traps and analyzed using Shannon-Wiener (H'), Simpson (C), and Pielou (E) indices. A total of 4,524 individuals representing 68 species, 31 families, and 9 orders were recorded. The riparian zone showed the highest diversity (H' = 3.41) and evenness (E = 0.83), while the forest interior had the highest dominance (C = 0.17) due to the prevalence of Hypoponera opaciceps. These findings indicate that high individual abundance does not necessarily equate to high biodiversity. The study concludes that habitat heterogeneity strongly influences soil insect community structure. Scientifically, the results highlight the need for habitat-based conservation strategies and support the use of soil insects as ecological indicators in tropical forest management.